1993
DOI: 10.2307/1942097
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production in a Tallgrass Prairie Ecosystem Exposed to Ambient and Elevated CO"2

Abstract: Responses to elevated CO"2 have not been measured for natural grassland ecosystems. Global carbon budgets will likely be affected by changes in biomass production and allocation in the major terrestrial ecosystems. Whether ecosystems sequester or release excess carbon to the atmosphere will partly determine the extent and rate that atmospheric CO"2 concentration rises. Elevated CO"2 also may change plant community species composition and water status. We determined above- and belowground biomass production, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(160 citation statements)
references
References 27 publications
9
149
2
Order By: Relevance
“…Most studies with undisturbed natural grassland communities under elevated CO 2 have yielded only marginally and frequently not signi®cant increases in community-level biomass (Owensby et al 1993;Navas et al 1995;Wolfenden and Diggle 1995). We observed a small increase (+6%) in aboveground community biomass in the ®rst, and a much larger increase (+26% ) in the second year of our experiment.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Most studies with undisturbed natural grassland communities under elevated CO 2 have yielded only marginally and frequently not signi®cant increases in community-level biomass (Owensby et al 1993;Navas et al 1995;Wolfenden and Diggle 1995). We observed a small increase (+6%) in aboveground community biomass in the ®rst, and a much larger increase (+26% ) in the second year of our experiment.…”
Section: Discussioncontrasting
confidence: 49%
“…The few studies with vegetation in undisturbed lowfertility soils have shown that the direct responses of community biomass to elevated CO 2 are usually much smaller than in agro-ecosystems, in some cases even zero (Owensby et al 1993;Jackson et al 1994;Navas et al 1995;Wolfenden and Diggle 1995;Leadley and KoÈ rner 1996;SchaÈ ppi and KoÈ rner 1996). Results from studies with species-rich model ecosystems indicate that community responses to elevated CO 2 may be low because highly positive responses of some species are dampened by small and sometimes negative responses of other species (Leadley and StoÈ cklin 1996;Roy et al 1996;StoÈ cklin et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extreme rainfall events may impair the trafficability of grassland, lead to more severe effects of treading and directly damage taller vegetation. Increased CO 2 concentrations in the atmosphere may have a growth-enhancing effect and at the same time may lead to improved water-use efficiency (Owensby et al, 1993;Soussana and Lü scher, 2007). Recent data indicate that grass vegetation can physiologically adjust to elevated atmospheric CO 2 concentrations as an adaptive response to the changing climate (Kö hler et al, 2010).…”
Section: Impacts On Quantity and Quality Of Fodder Productionmentioning
confidence: 99%
“…In our study this species-specific effect persisted over the 3-year experimental period, despite some season to season variation. It has been proposed that a lower leaf-nitrogen content observed under elevated CO 2 in crop species (Wong 1979;Conroy, Milham & Barlow 1992), as well as in tall grass prairie vegetation (Owensby, Coyne, Ham et al 1993), reflects an increase of plants nitrogen-use efficiency. In alpine grasslands, belowground biomass accounts for a large part of the nitrogen pool and an estimate of nitrogen-use efficiency can only be carried out on a total biomass basis.…”
Section: Nitrogen Concentrations and Nitrogen Pools In The Biomass Pementioning
confidence: 99%
“…Enhanced microbial nitrogen immobilization in the soil and thus a CO 2 -induced decrease in nitrogen availability may cause a decrease of nitrogen in the leaves (Diaz et al 1993, but see Niklaus & Körner 1996;. Apart from CO 2 related decreases in foliage nitrogen, decreases in nitrogen per biomass have also been detected at the whole plant level and, thus, a reduction in nitrogen demand under CO 2 enrichment has been proposed (Owensby, Coyne, Ham et al 1993).…”
Section: Introductionmentioning
confidence: 99%